2010
DOI: 10.1007/s00276-010-0639-z
|View full text |Cite
|
Sign up to set email alerts
|

Chiari’s network: review of the literature

Abstract: The Chiari network, present in approximately 2% of the population, and is a reticulated network of fibers originating from the Eustachian connecting to different parts of the right atrium. Its presence results from incomplete reabsorption of the right valve of the sinus venosus. Chiari's network is often clinically insignificant. However, it has been reported to be involved in the pathogenesis of thromboembolic disease, endocarditis, arrhythmias, and entrapment of catheters upon percutaneous intervention. Whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
97
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(100 citation statements)
references
References 30 publications
1
97
1
1
Order By: Relevance
“…Right atrial anomalous bands, which are the so-called Chiari’s network, are reported to cause supraventricular arrhythmias 4 . The left ventricular anomalous band or false tendon has been reported to cause specific types of ventricular arrhythmias 5, 6.…”
Section: Discussionmentioning
confidence: 99%
“…Right atrial anomalous bands, which are the so-called Chiari’s network, are reported to cause supraventricular arrhythmias 4 . The left ventricular anomalous band or false tendon has been reported to cause specific types of ventricular arrhythmias 5, 6.…”
Section: Discussionmentioning
confidence: 99%
“…The Chiari network, an embryonic remnant from the persistence of the right valve of the sinus venosus, was first described in 1897 1 2. It is reported to occur in 2% of the population, although more recently was observed in 13.6% of 213 cadaver hearts and 10% of the 38 hearts that were autopsied 3.…”
Section: Discussionmentioning
confidence: 99%
“…Anatomical variations may have profound effects on both the performance and deployment of cardiac devices; thus a well-developed understanding of the relevant cardiovascular anatomies (in relation to both vascular approaches and within the heart itself) is critical at all levels of the device design and development process [3][4][5]. Our laboratory has the privilege to obtain fresh human heart specimens for educational and research purposes from: (1) organ donors whose hearts are not deemed viable for transplantation and donated for research (via LifeSource, the Upper Midwest Organ Procurement Organization); and (2) bodies donated to the University of Minnesota's Anatomy Bequest Program.…”
Section: General Methodologiesmentioning
confidence: 99%